Blockchain Applications Transforming Industries, Enhancing Security, and Addressing Ethical Considerations - Chernyshenko, Vsevolod; Mkrttchian, Vardan (IntechOpen, 2023)
Unlock the transformative power of blockchain technology with Blockchain Applications - Transforming Industries, Enhancing Security, and Addressing Ethical Considerations. This edited volume brings together leading experts and their thought-provoking chapters on blockchain's diverse applications. From healthcare to finance and from energy to supply chain, delve into the latest advancements in cybersecurity, smart contracts, and audit digitalization. Discover how blockchain is revolutionizing the tourism industry and enabling decentralized autonomous organizations. Explore the potential of deep learning for disease detection and gain insights into the legal and market challenges of non-fungible tokens (NFTs). With real-world examples and case studies, this book showcases blockchain's tangible benefits, which include increased transparency, enhanced security, and improved efficiency. It also improves understanding of the ethical considerations and regulatory implications surrounding blockchain adoption for responsible implementation. This invaluable resource is for professionals, researchers, and technology enthusiasts alike, offering unique perspectives and cutting-edge research. Join us on a captivating journey through the world of blockchain applications. Experience its potential to reshape industries, enhance security, and pave the way for a transparent and decentralized future. Discover the keywords defining this volume: blockchain technology, transformative potential, cybersecurity, smart contracts, decentralized autonomous organizations, deep learning techniques, non-fungible tokens, transparency, security, efficiency, ethical considerations, regulatory implications, real-world examples, and cutting-edge research. Embrace the revolution and unlock the limitless possibilities of blockchain technology.